Case Report: A rare case of thyroid metastasis from breast cancer - Gao, Xiaochuan; Li, Mengxin; Hong, Jinghui; Wu, Yuheng; Fu, Tong; Song, Dong (Frontiers in Oncology, 2025)
IntroductionTo analyze the clinicopathological features, diagnosis, and treatment strategies for metastatic breast carcinoma to the thyroid (MBCT) to enhance clinical awareness of this rare condition.MethodsAnalysis of clinical data from one MBCT patient and literature review.ResultsA 41-year-old female with left breast invasive ductal carcinoma (IDC) received neoadjuvant AC-T chemotherapy, breast-conserving surgery, radiotherapy, and endocrine therapy. At eight years post-diagnosis, thyroid lesions were detected. Total thyroidectomy with lymph node dissection confirmed MBCT pathologically. No progression was observed at 16 months post-thyroidectomy.ConclusionsMBCT is a rare clinical entity characterized by nonspecific clinical and radiological findings. Immunohistochemical (IHC) analysis is essential for a definitive diagnosis. In patients with a breast cancer history, MBCT should always be considered in the differential diagnosis of thyroid abnormalities.